Burning increases post-fire carbon emissions in a heathland and a raised bog, but experimental manipulation of fire severity has no effect. (1st March 2019) - Grau-Andrés, Roger; Gray, Alan; Davies, G. Matt; Scott, E Marian; Waldron, Susan
Abstract: Large amounts of carbon are stored in northern peatlands. There is concern that greater wildfire severity following projected increases in summer drought will lead to higher post-fire carbon losses. We measured soil carbon dynamics in a Calluna heathland and a raised peat bog after experimentally manipulating fire severity. A gradient of fire severity was achieved by simulating drought in 2 × 2 m plots. Ecosystem respiration (ER), net ecosystem exchange (NEE), methane (CH4 ) flux and concentration of dissolved organic carbon ([DOC], measured at the raised bog only) were measured for up to two years after burning. The response of these carbon fluxes to increased fire severity in drought plots was similar to plots burnt under ambient conditions associated with traditional managed burning. Averaged across all burnt plots, burning altered mean NEE from a net carbon sink at the heathland (−0.33 μ mol CO2 m −2 s −1 in unburnt plots) to a carbon source (0.50 μ mol m −2 s −1 in burnt plots) and at the raised bog (−0.38 and 0.16 μ mol m −2 s −1, respectively). Burning also increased CH4 flux at the raised bog (from 1.16 to 25.3 nmol m −2 s −1 in the summer, when it accounted for 79% of the CO2 -equivalent emission). Burning had no significant effect on soil water [DOC]. Highlights: Experimental burning increased short-term CO2 and CH4 emissions. Higher fire severity after simulated drought had no effect on post-fire C fluxes. Fire had no effect on porewater DOC concentration at the raised bog.